The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/plants11010088
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic Significance of Seed Morphology in Veronica L. (Plantaginaceae) Species from Central Europe

Abstract: In this study, 1159 seeds of 29 Central European species of the genus Veronica were analyzed based on scanning electron microscopy images. The species belonged to nine subgenera: Beccabunga, Chamaedrys, Cochlidiosperma, Pellidosperma, Pentasepalae, Pocilla, Pseudolysimachium, Stenocarpon and Veronica, following the newest phylogenetic classification of the genus. Nine measured characteristics of seeds and nine ratios were analyzed statistically using ANOVA followed by post hoc testing, cluster analysis and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Clustering methods were efficient in verifying the existence of genetic variability and similarity between genotypes as well as the principal component to concentrate the number of variables to facilitate the interpretation of results. The results obtained through seed image analysis and multivariate analysis showed that seeds provide important information about the adaptation and evolution of Anchusa L. taxa in Sardinia (Farris et al, 2020), and helped to identify seeds from different locations (Pan et al, 2021;Cecco, Musciano, D'Archivio, Frattaroli, & Martino, 2019), and the distribution of species from Central Europe (Mazur, Marcysiak, Dunajska, Gawlak, & Kałuski, 2022). In the present study, seeds from closer populations also presented similar biometric characteristics.…”
Section: Discussionsupporting
confidence: 66%
“…Clustering methods were efficient in verifying the existence of genetic variability and similarity between genotypes as well as the principal component to concentrate the number of variables to facilitate the interpretation of results. The results obtained through seed image analysis and multivariate analysis showed that seeds provide important information about the adaptation and evolution of Anchusa L. taxa in Sardinia (Farris et al, 2020), and helped to identify seeds from different locations (Pan et al, 2021;Cecco, Musciano, D'Archivio, Frattaroli, & Martino, 2019), and the distribution of species from Central Europe (Mazur, Marcysiak, Dunajska, Gawlak, & Kałuski, 2022). In the present study, seeds from closer populations also presented similar biometric characteristics.…”
Section: Discussionsupporting
confidence: 66%
“…Descriptive terminology for fruit and seed characters followed Stearn (1983), Barthlott (1984), Verma & al. (2017), Mazur & al. (2021).…”
Section: Fruit and Seed Observation And Measurementsmentioning
confidence: 99%
“…Fruit and seed morphology has been long recognized as important for classification and can be successfully used in identification, taxonomic circumscription and phylogenetic implication (Arambarri 2000;Mazur & al. 2021;among others).…”
Section: Introductionmentioning
confidence: 99%
“…Veronica L. is the largest genus in the flowering plant family Plantaginaceae, with about 500 species distributed in the world (Mazur et al. 2021 ). However, there were only six plastomes sequenced and submitted to GenBank (retrieved July 2022 from https://www.ncbi.nlm.nih.gov ), which hinder to resolve the phylogeny of Veronica.…”
mentioning
confidence: 99%